Consumption of ultra-processed foods and risk of multimorbidity of cancer and cardiometabolic diseases - Cordova, Reynalda (2023)
Funding Information: The coordination of EPIC is financially supported by International Agency for Research on Cancer (IARC) and also by the Department of Epidemiology and Biostatistics, School of Public Health, Imperial College London which has additional infrastructure support provided by the NIHR Imperial Biomedical Research Centre (BRC). The national cohorts are supported by: Danish Cancer Society (Denmark); Ligue Contre le Cancer , Institut Gustave-Roussy , Mutuelle Générale de l'Education Nationale , Institut National de la Santé et de la Recherche Médicale (INSERM) (France); German Cancer Aid , German Cancer Research Center (DKFZ), German Institute of Human Nutrition Potsdam-Rehbruecke (DIfE), Federal Ministry of Education and Research (BMBF) (Germany); Associazione Italiana per la Ricerca sul Cancro -AIRC-Italy, Compagnia di SanPaolo and National Research Council (Italy); Dutch Ministry of Public Health, Welfare and Sports (VWS), Netherlands Cancer Registry (NKR), LK Research Funds , Dutch Pittsburgh Foundation , Dutch ZON (Zorg Onderzoek Nederland), World Cancer Research Fund (WCRF), Statistics Netherlands (The Netherlands); Health Research Foundation (FIS)– Instituto de Salud Carlos III (ISCIII), Regional Governments of Andalucía, Asturias, Basque Country, Murcia and Navarra, and the Catalan Institute of Oncology –ICO (Spain); Swedish Cancer Society , Swedish Research Council and County Councils of Skåne and Västerbotten (Sweden); Cancer Research UK (14136 to EPIC-Norfolk; C8221/A29017 to EPIC-Oxford), Medical Research Council (1000143 to EPIC-Norfolk; MR/M012190/1 to EPIC-Oxford). (United Kingdom). Funding Information: Austrian Academy of Sciences, Fondation de France, Cancer Research UK, World Cancer Research Fund International, and the Institut National du Cancer.The authors would like to thank the EPIC study participants and staff for their valuable contribution to this research. The authors would also like to especially thank Fernanda Rauber, Eszter P. Vamos, and Kiara Chang for their contribution to implement the Nova classification in the EPIC study, and Bertrand Hemon and Corinne Casagrande for preparing the EPIC databases. We acknowledge the use of data from the EPIC-Aarhus cohort, PI Kim Overvad; the EPIC-Asturias cohort, PI J. Ramón Quirós; the EPIC-Umea cohort, PIs Mattias Johansson und Malin Sund; the EPIC-Norfolk cohort; and the National Institute for Public Health and the Environment (RIVM), Bilthoven, the Netherlands, for their contribution and ongoing support to the EPIC Study. Funding: Reynalda Cordova is a recipient of a DOC Fellowship of the Austrian Academy of Sciences. This study was financially supported by the Fondation de France (FDF, grant no. 00081166, HF). This work was also supported by Cancer Research UK (C33493/A29678), the World Cancer Research Fund International (IIG_FULL_2020_033), and the Institut National du Cancer (INCa no. 2021–138). The coordination of EPIC is financially supported by International Agency for Research on Cancer (IARC) and also by the Department of Epidemiology and Biostatistics, School of Public Health, Imperial College London which has additional infrastructure support provided by the NIHR Imperial Biomedical Research Centre (BRC). The national cohorts are supported by: Danish Cancer Society (Denmark); Ligue Contre le Cancer, Institut Gustave-Roussy, Mutuelle Générale de l'Education Nationale, Institut National de la Santé et de la Recherche Médicale (INSERM) (France); German Cancer Aid, German Cancer Research Center (DKFZ), German Institute of Human Nutrition Potsdam-Rehbruecke (DIfE), Federal Ministry of Education and Research (BMBF) (Germany); Associazione Italiana per la Ricerca sul Cancro-AIRC-Italy, Compagnia di SanPaolo and National Research Council (Italy); Dutch Ministry of Public Health, Welfare and Sports (VWS), Netherlands Cancer Registry (NKR), LK Research Funds, Dutch Pittsburgh Foundation, Dutch ZON (Zorg Onderzoek Nederland), World Cancer Research Fund (WCRF), Statistics Netherlands (The Netherlands); Health Research Foundation (FIS)–Instituto de Salud Carlos III (ISCIII), Regional Governments of Andalucía, Asturias, Basque Country, Murcia and Navarra, and the Catalan Institute of Oncology–ICO (Spain); Swedish Cancer Society, Swedish Research Council and County Councils of Skåne and Västerbotten (Sweden); Cancer Research UK (14136 to EPIC-Norfolk; C8221/A29017 to EPIC-Oxford), Medical Research Council (1000143 to EPIC-Norfolk; MR/M012190/1 to EPIC-Oxford). (United Kingdom). Disclaimer: Where authors are identified as personnel of the International Agency for Research on Cancer/World Health Organization, the authors alone are responsible for the views expressed in this article and they do not necessarily represent the decisions, policy or views of the International Agency for Research on Cancer/World Health Organization. Funding Information: Funding: Reynalda Cordova is a recipient of a DOC Fellowship of the Austrian Academy of Sciences. This study was financially supported by the Fondation de France (FDF, grant no. 00081166 , HF). This work was also supported by Cancer Research UK (C33493/A29678), the World Cancer Research Fund International (IIG_FULL_2020_033), and the Institut National du Cancer (INCa no. 2021–138). Publisher Copyright: © 2023